Estimation of reliability of structures subject to fatigue loading using plastic strain energy and thermodynamic entropy generation. (June 2015) - Ontiveros, Victor Luis; Modarres, Mohammad; Amiri, Mehdi
Plastic strain energy dissipation and thermodynamic entropy generation are explored as means of estimating the likelihood of fatigue crack initiation in reliability assessment of structures. A set of experimental data for aluminum alloy 7075-T651 used in airframe structures are presented to determine the correlation between plastic strain energy dissipation and the thermodynamic entropy generation versus fatigue crack initiation. Cumulative plastic strain energy and thermodynamic entropy generation measured from hysteresis energy and temperature rise proved to be valid physical indices for estimation of the probability of crack initiation. Crack initiation is considered as evidence of fatigue damage and loss of structural integrity. A Bayesian estimation and validation approach is used to determine systematic errors in the developed models as well as other model uncertainties. It was shown that the results from both methods are good predictors of crack initiation and comparable, but the entropy generation method was associated with fewer uncertainties than the plastic strain energy method. Comparisons of the energy-based and entropy-based models are presented and advantages of using one over the other are discussed.